Influence of pH levels and beverage exposure on force decay and color stability of orthodontic elastomeric chains: An experimental study - Tadeja Blagec; Luka Šimunović; Sandra Pili Gjumlić; Ivana Šutej; Senka Meštrović (Saudi Dental Journal)
Aim of study: To assess the impact of pH level on force decay and color stability of orthodontic elastomeric chains (EOC) after exposure to commonly used beverages. Materials and methods: A total of 120 chain cuts were prepared from 2 different manufacturers (GC Orthodontics Europe GmbH, Breckerfeld, Germany, and FORESTADENT® - Bernhard Foerster GmbH, Pforzheim, Germany). According to the distance between loops, two types of chains were selected from each manufacturer: short and medium ones. Chains were immersed into 10 commonly used beverages with different pH values. After 7 days, force degradation was evaluated with the universal machine for mechanical testing (Model 4411; Instron, Canton, USA) and color change using a VITA Easyshade® digital spectrophotometer. Kruskal-Wallis with post-hoc Dunn's test for intergroup comparison and Wilcoxon rank test for intragroup comparison. Results: Initial force varied among EOC brands, with GC short chains having the highest force and Forestadent medium chains the lowest. The most pronounced force decay occurred within 24 h, notably affecting Forestadent short chains the most, followed by Forestadent medium, GC short, and GC medium chains. Despite a higher force drop rate over seven days, short EOCs maintained higher forces than medium EOCs. GC EOCs consistently maintained higher forces after seven days compared to Forestadent EOCs. After the immersion of EOC in different solutions for 24 h, only Evian water, Soy milk, and Coconut water did not change color. After 7 days, the greatest color change was recorded in coffee. Conclusion: There is no correlation between pH value and force decay of polyurethane chains. Short chains showed more constant force delivery and greater value of remaining force in comparison to medium ones. Color stability was mostly affected by coffee, followed by matcha tea, soy milk, and apple juice.